The effect of perceptual training with anxiety on the anticipatory judgments of elite badminton players - Alder, D.; Causer, J.; Ford, P. R. (World Badminton Federation, 2016)
Sport performance is negatively affected when performers become anxious. Researchers have shown that training during which participants are made to experience high anxiety can protect against its negative effects (e.g., Causer, Holmes, Smith, & Williams, 2011). Anticipation is a key part of expert badminton performance and necessitates that players `read the game` to perceive ahead of an action occurring what their opponent is likely to do in any particular situation. Anticipatory judgments can be improved through training interventions, including those using video simulation (e.g., Williams, Ward, Knowles & Smeeton, 2002). The aim of this study was to examine the training of anticipation in badminton using video simulation under anxious conditions and the transfer of learning to high anxiety conditions and the field.